2010
DOI: 10.1007/s13197-010-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Tenderizing effect of blade tenderizer and pomegranate fruit products in goat meat

Abstract: Toughness of goat meat is a major problem with regard to consumer acceptance. Keeping this in view a blade tenderizer was developed for tenderization of goat meat. Pomegranate fruit products were also explored for tenderization effect on goat meat. Tenderization of goat meat with pomegranate seed powder improved the textural properties marginally with slight adverse colour change and taste. Samples treated with PRP got lower score for colour in sensory evaluation and there was adverse effect on taste of treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…Meanwhile, the highest OA score in PG treatments was 3% and 5 % peel&molasses mix MB (9.34±0.09 and 9.20±0.18 respectively), followed by 5% molasses MB and 3% peel MB (9.10±0.15 and 9.06±0.13, respectively). These findings were partially similar to those obtained by Narsaiah et al (2011) who indicated that tenderidazation of goat meat with PG seed powder (PSP) improved the textural products properties, however got lower score for color in sensory evaluation and there was adverse effect on taste of treated meat. Devatkal et al 2010 also observed similar darkening of goat meat patties containing PG products which agree with our results.…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, the highest OA score in PG treatments was 3% and 5 % peel&molasses mix MB (9.34±0.09 and 9.20±0.18 respectively), followed by 5% molasses MB and 3% peel MB (9.10±0.15 and 9.06±0.13, respectively). These findings were partially similar to those obtained by Narsaiah et al (2011) who indicated that tenderidazation of goat meat with PG seed powder (PSP) improved the textural products properties, however got lower score for color in sensory evaluation and there was adverse effect on taste of treated meat. Devatkal et al 2010 also observed similar darkening of goat meat patties containing PG products which agree with our results.…”
Section: Resultssupporting
confidence: 88%
“…Both instrumental and sensory evaluation of cooked meat samples showed increased tenderness of SMP and MP group than control groups. Similar results observed when goat meat was marinating with pomegranate seed extract which affected the physicochemical and sensory attributes of raw goat meat (Narsaiah et al 2011).…”
Section: Sensory Analysissupporting
confidence: 73%
“…Pawar et al (2003) observed similar trend for chevon tenderized by papain. Narsaiah et al (2011) did same experiment with pomegranate seed powder and pomegranate rind powder and observed tenderness scores were significantly higher in treated samples than control. Mendiratta et al (2000) found reduction in shear force values with ginger extract treatment in sheep meat.…”
Section: Shear Force Measurement (Tenderness Value)mentioning
confidence: 91%
See 1 more Smart Citation
“…The previous study also found that reduction in pH of buffalo meats treated Cucumis trigonus Roxb (Kachri) compared to control [18]. The pH of goat meat treated with 4% pomegranate seed powder was reduced as reported by Narsaiah et al [19]. Burke and Monahan [14] also reported a significant reduction in pH of bovine muscle strips marinated with citrus juice marinade compared to the untreated sample.…”
Section: Physicochemical Characteristicsmentioning
confidence: 54%